2010
DOI: 10.1007/s10706-010-9329-1
|View full text |Cite
|
Sign up to set email alerts
|

Stone Columns with Vertical Circumferential Nails: Laboratory Model Study

Abstract: This paper presents results from a series of laboratory plate load tests carried out in unit cell tanks to investigate the improvement in stiffness, load carrying capacity and resistance to bulging of stone columns installed in soft soils. A new method of reinforcing the stone columns with vertical nails installed along the circumference of the stone column is suggested for improving the performance of these columns. Tests were carried out with two types of loading (1) the entire area in the unit cell tank loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Many authors [24][25][26][27] performed field scale load tests on vertical encased granular piles; however no literature is available on in situ tests carried out on granular piles reinforced with horizontal strips. Shivashankar et al [28] investigated granular piles reinforced with vertical nails and found higher load carrying capacity and lesser bulging as compared to ordinary granular piles. Kumar et al [29] studied combined effect of vacuum consolidation and geosynthetic encased granular piles and observed that both stiffness and load carrying capacity of the piles increase significantly after the application of vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors [24][25][26][27] performed field scale load tests on vertical encased granular piles; however no literature is available on in situ tests carried out on granular piles reinforced with horizontal strips. Shivashankar et al [28] investigated granular piles reinforced with vertical nails and found higher load carrying capacity and lesser bulging as compared to ordinary granular piles. Kumar et al [29] studied combined effect of vacuum consolidation and geosynthetic encased granular piles and observed that both stiffness and load carrying capacity of the piles increase significantly after the application of vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…Stone columns are installed in wide variety of soils, ranging from loose sands to soft compressible clays (Shivashankar et al, 2010). The beneficial effects of stone columns on their loadsettlement characteristics of reinforcing soft clay deposits have been widely demonstrated by several researchers (Engelhardt et al, 1974;DiMaggio, 1978;Han and Ye, 2001;McKelvey et al, 2004;Castro and Karstunen, 2010;Murugesan and Rajagopal, 2010;Cimentada et al, 2011;Deb et al, 2011;Fattah et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although the column diameter and the unit cell diameter can affect the Ar, the studies with variable D e values concentrated on the effect of SC spacing, while those with variable d values concentrated on the effect of the SC diameter. [37] 158, 283 750 720 D, d Subramaniyan and Masoodhu [38] 280 310 310 60 Sudheer et al [39] 210 280 210 50 Suriya et al [40] 150 220 220 -Tallapragada et al,2011 [41] 100 300 300 -…”
Section: Testing Tankmentioning
confidence: 99%
“…Inserting nails vertically along the perimeter of the SC is suggested as a form of reinforcement [17,37]. For the geosynthetic fabrics, the tensile strength, the aperture size, the thickness and, the weight per unit length can usually be provided by the manufacturer.…”
Section: Reinforcement Materialsmentioning
confidence: 99%